ErbBs inhibition by lapatinib blocks tumor growth in an orthotopic model of human testicular germ cell tumor. Issue 1 (12th February 2013) - Juliachs, M.; Castillo‐Ávila, W.; Vidal, A.; Piulats, J.M.; Garcia del Muro, X.; Condom, E.; Hernández‐Losa, J.; Teixidó, C.; Pandiella, A.; Graupera, M.; Casanovas, O.; Germà, J.R.; et al.
<x xml:space="preserve">Abstract</x> In this work, we have analyzed the expression of different members of the ErbB family in human samples of testicular germ cell tumors (GCTs). We observed expression of ErbB1 or ErbB2 in different tumor subtypes, but we also found high expression of ErbB3 in all GCTs tested. This pattern of expression was maintained when primary tumors were orthotopically implanted in nude mice. We have chosen a choriocarcinoma model characterized by high levels of ErbB1, but also of ErbB2 and ErbB3, to assay the in vivo effect of ErbB inhibitors on tumoral growth. Our results showed a complete lack of effect (refractoriness) to the pure ErbB1 receptor inhibitors cetuximab and gefitinib. While these inhibitors blocked ErbB1 phosphorylation, ErbB2 phosphorylation was not affected, suggesting an ErbB1‐independent activation of this receptor. To confirm the importance of ErbB2 activation, animals were treated with lapatinib, a dual ErbB1 and ErbB2 inhibitor. Lapatinib treatment caused a 50% inhibition in tumor growth, an effect correlated with a blockade of both ErbB1 and ErbB2 phosphorylation levels, and of downstream signaling pathways (Akt, ERKs and Stat3). ErbB2 activation could still occur due to the formation of ErbB2/ErbB3 heterodimers, and ErbB3 activation was completely inhibited by lapatinib. Finally, combined inhibition of ErbB1 (gefitinib) and ErbB3 activities (knockdown expression by shRNA) inhibited tumoral testicular cells proliferation in a similar way to lapatinib. Our results explain why lapatinib but not anti‐ErbB1 agents might be effective for treatment of testicular GCT patients.